Extended state observer based control for DC motors - Y. Borkar, Ajay; P.M Patil, Dr. (International Journal of Engineering and Technology, 2019)
In this paper, an extended state observer (ESO) based control is derived for the position control of permanent magnet direct current (PMDC) motor. The implementation of the proposed control law requires only position sensor. The estimation of states and disturbance is achieved by ESO. The closed loop stability of the proposed scheme is derived. The performance of observer-controller is verified in the presence of uncertainties and load disturbance.Â Â